Schwarzian derivative as a proof of the chaotic behaviour - Ozdemir, Zeynep Guven (INDIAN ACAD SCIENCES, 2011)
In recent years, a sufficient condition for determining chaotic behaviours of the nonlinear systems has been characterized by the negative Schwarzian derivative (Hacibekiroglu et al, Nonlinear Anal.: Real World Appl. 10, 1270 (2009)). In this work, the Schwarzian derivative has been calculated for investigating the quantum chaotic transition points in the high-temperature superconducting frame of reference, which is known as a nonlinear dynamical system that displays some macroscopic quantum effects. In our previous works, two quantum chaotic transition points of the critical transition temperature, T(c), and paramagnetic Meissner transition temperature, T(PME), have been phenomenologically predicted for the mercury-based high-temperature superconductors (Onbasli et al, Chaos, Solitons and Fractals 42, 1980 (2009); Asian et al, J. Phys.: Conf. Ser 153, 012002 (2009); cataltepe, Superconductor (Sciyo Company, India, 2010)). The T(c), at which the one-dimensional global gauge symmetry is spontaneously broken, refers to the second-order phase transition, whereas the T(PME), at which time reversal symmetry is broken, indicates the change in the direction of orbital current in the system (Onbasli et al, Chaos, Solitons and Fractals 42, 1980 (2009)). In this context, the chaotic behaviour of the mercury-based high-temperature superconductors has been investigated by means of the Schwarzian derivative of the magnetic moment versus temperature. In all calculations, the Schwarzian derivatives have been found to be negative at both T(c) and T(PME) which are in agreement with the chaotic behaviour of the system.
Keywords: Mercury cuprate superconductors; nonlinear dynamics and chaotic behaviour; Schwarzian derivative; paramagnetic Meissner effect; LONG JOSEPHSON-JUNCTIONS; TRANSITION; Physics